Some slaughter characteristics of the mallard (Anas p. platyrhynchos, L. 1758) - Szász, Sándor; Sugár, László; Pőcze, Olga; Ujvári, Jolán; Taraszenkó, Zsuzsanna (Acta Agraria Kaposváriensis, 2006)
Three subspecies of the mallard (Anas p. platyrhynchos, L. 1758) are typical nesting birds in the Holarctic. The mallard is our most important warefowl and will probably keep this position in the future. Because of the very few literature sources it seemed to be reasonable to examine the so called important poultry-industrial characteristics of the mallard in both sexes, like the carcass weight, valuable meat (carcass) parts, slaughter losses etc Altogether 24 mallards shot were examined. After the wet placking the carcasses were opened, eviscerated and dissection according to the method used in poultry processing (Jensen, 1983). The body weight (shot) and weight of brest and thighs with skin as well as the weight of brest fillet and thigh fillet were weighed. The average values of the carcass weight for the two sexes were ♂1228 ± 160 g; ♀1058 ± 98 g. The weight data of the breast with skin were 256 ± 33 g in drakes and 239 ± 36 g in ducks (p < 0.05). The breast fillet weight were 167 ± 28 g and 153 ± 24 g respectively. The weight data of the thighs with skin were 138 ± 14 g in drakes and 119 ± 12 g in ducks. The weight data of the thigh fillet were ♂80 ± 12 g and ♀65 ± 6 g respectively (p < 0.05).